Dificuldades operacionais causadas pela falta de alinhamento dos sistemas ERP com os processos de negócio: múltiplos estudos de casos em concessionárias de veículos - Morgado, Flávio (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper presents a study on the operational difficulties caused by the lack of alignment between ERP systemsand business processes, performed along with managers and other evidence sources of a specific type of organization,the Brazilian car dealers. The methodology selected was the multiple case studies. The car dealers werechosen due to their size, their relations with other dealers, the brands they represent, the management systemsthey use, their segment and the region they operate in. The informatized management systems are responsiblefor the automation of tasks, and they should contribute to a greater productivity and flexibility of the processes.However, they are sub-utilized, thus generating parallel controls, which impair the information flow for theperformance analysis and for the decision-making process. The deficiencies in the informatized systems and thepoorly-defined processes make that controls, conferences, retyping, conciliations, error treatment and reworksoccur in the majority of the administrative work. Such deficiencies are aggravated due to insufficient or impropertraining, and due to the fact that organization manuals are not used.Keywords: ERP systems; Business Processes; Operational Difficulties; Car Dealers.